INTERPRETATION OF METAPHORS IN SONG LYRICS BY EFL STUDENTS - Cardoso, Gisele Luz (2010)
This study focuses on the process of co-construction of meanings of metaphorical expressions in a song lyric by EFL students. Think-aloud protocols were recorded and analyzed qualitatively. The analysis showed that while readers discussed the lyric in groups, they could identify a conceptual metaphor underlying conventional metaphorical expressions.